Infection of nonclassic monocytes by respiratory syncytial virus induces an imbalance in the CD4+ T-cell subset response - Lianlian Han; Danyang Li; Conghui Wang; Lili Ren; Li Guo; Jianwei Wang (Microbiology Spectrum)
ABSTRACT Respiratory syncytial virus (RSV) causes lower respiratory tract infections in infants and young children, leading to a pathogenesis-associated imbalance in CD4+ T-cell subsets and monocyte subsets. To investigate whether RSV affects the imbalance of CD4+ T-cells through monocytes, we examined the effects of the RSV-infected monocyte subset on CD4+ T-cell subsets, namely, Th1, Th2, Th17, and regulatory T (Treg) subsets, on proliferation in vitro and identified key monocyte-derived cytokines. We found that RSV efficiently infects CD16+ monocytes, but not CD16- monocytes, via cocultures of CD4+ T-cells with RSV-infected CD16+ monocytes, inhibits Treg cell proliferation and increases Th2 cell frequency, suggesting that RSV causes an imbalance in the CD4+ T-cell subset by primarily infecting CD16+ monocytes. Our data also revealed that IL-1β and IL-10 are key cytokines responsible for the activities of RSV-infected CD16+ monocytes. In a mouse model, we found that high-efficiency RSV infection of mouse Ly6C- monocytes, corresponding to CD16+ monocytes in humans, and adoptive transfer of Ly6C- monocytes during RSV infection decreased the Treg frequency in the lungs and aggravated pneumonia. Our data indicate that RSV can increase its pathogenesis through infection of nonclassic monocytes, leading to a CD4+ T-cell imbalance.IMPORTANCEThis study identified a pathogenesis pathway related to the RSV-nonclassic monocyte–IL-1β/IL-10-CD4+ T-cell subset balance, which links the heterogeneity of monocytes to RSV pathogenesis and elucidates a new mechanism by which RSV infection disrupts the balance of CD4+ T cells during RSV infection. These new findings provide potential therapeutic targets for RSV infection.